2014
DOI: 10.1002/anie.201403918
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Triarylboron Compound for ATP Imaging In Vivo Using Analyte‐Induced Finite Aggregation

Abstract: Adenosine 5'-triphosphate (ATP) is a multifunctional molecule that participates in many important biological processes. Currently, fluorescence indicators for ATP with high performance are in demand. Reported herein is a novel water-soluble triarylboron compound which displays an apparent ATP-dependent fluorescence enhancement when dispersed in water. It can selectively recognize ATP from other bioactive substances in vitro and in vivo. The ATP-induced finite aggregation endows the indicator with appreciable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…5, apparent fluorescence signal occurred in the cytoplasm and cell membrane, but not in the nucleus. The distribution of ATP is in line with the reported (Ojida et al, 2002(Ojida et al, , 2006(Ojida et al, , 2008Li et al, 2014). To further confirm that fluorescent domain was triggered by ATP, apyrase was used to treat the cells prior to the staining procedure.…”
Section: The Atp Detection In Living Cells By Fluorescent Imagessupporting
confidence: 82%
See 2 more Smart Citations
“…5, apparent fluorescence signal occurred in the cytoplasm and cell membrane, but not in the nucleus. The distribution of ATP is in line with the reported (Ojida et al, 2002(Ojida et al, , 2006(Ojida et al, , 2008Li et al, 2014). To further confirm that fluorescent domain was triggered by ATP, apyrase was used to treat the cells prior to the staining procedure.…”
Section: The Atp Detection In Living Cells By Fluorescent Imagessupporting
confidence: 82%
“…We also reported a molecular assembly of a squaraine dye with cationic surfactant for selectively fluorescence response to ATP (Xu et al, 2011). Very recently, Yang and coworkers reported a water-soluble triarylboron compound for ATP imaging through analyte-induced finite aggregation (Li et al, 2014). These sensors take advantage of different receptors binding, i.e., hydrogen bonding, electrostatic interactions, π-π interactions, or combinations of them, to achieve good selectivity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They and two other groups made use of a similar method for the preparation of water‐soluble triarylboranes with phosphonium substituents for anion sensing . Recently, a water‐soluble, non‐ionic triarylborane containing polyethylene glycol chains as the hydrophilic groups was reported by Yang and co‐workers as an efficient fluorescence indicator for ATP in the cytoplasm and cell membrane . Furthermore, while our work was in progress, the same authors reported a water‐soluble triarylborane‐containing Cu II ‐cyclen.…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, p-conjugated triarylboron derivatives show high fluorescence quantum yield and excellent photostability. Triarylboron luminogens, therefore, have promising applications in diverse areas, such as temperature measurement [24][25][26], adenosine triphosphate (ATP) detection [27], fluoride detection [28] and two-photon absorption antenna [29]. Considering outstanding features of p-conjugated triarylboron derivatives, we designed and synthesized a "turn-on" twophoton fluorescent probe DMDP-M (Scheme 1) based on a p-conjugated triarylboron luminogen 4-(dimesitylboryl)-N,Ndiphenylaniline (DMDP) bearing a maleimide moiety linked by methylene spacer for selective detection of thiols.…”
Section: Introductionmentioning
confidence: 99%